HONOUR, DIGNITY AND REPUTATION AS OBJECTS OF CRIMINAL LAW PROTECTION - N. B. Guliyeva (Вестник Кемеровского государственного университета, 2015)
Legal protection of interests of the individual is one of the priority directions of activity of the state. Honour, dignity and reputation form an inherent ethical component of the personality structure. Criminal law protection of honour, dignity and reputation is performed by criminalizing the acts that are dangerous for such objects. Criminal law protects intangible benefits ща ordinary citizens and special subjects. The need for the existence and delineation of such legislative constructions is socially determined. In this paper the concepts of honour and dignity are defined; the existing legal and other scientific definitions of the studied categories are analyzed, the author’s own judgment is suggested. The author used the research methods of analysis, synthesis, method of comparative law. The present study can be used in law enforcement and research activities in the educational process.